Answer:
Honey I don't see nothing:)
Answer:
128
Step-by-step explanation:
Answer:
let x = 0
therefore
24=4(0)+6y
24=0+6y
24=6y
y= 24/6
y=4
you can take different value of x and the value of y will change automatically
f(x) > 0 - I and II quadrant
f(x) < 0 - III and IV quadrant
Look at the picture.
A. F(x) < 0 on the interval x < 0. TRUE
B. F (x) > 0 on the interval x <0. FALSE
C. F (x) < 0 on the interval 0 < x < 1. TRUE
D. F (x) > 0 on the interval 0 < x < 1. FALSE
E. F (x) < 0 on the interval 1 < x < 3. FALSE
F. F (x) > 0 on the interval 1 < x < 3. TRUE
G. F (x) < 0 on the interval x > 3. TRUE
H. F (x) > 0 on the interval x > 3. FALSE